Exposure to pornography in relation to men's sexism towards women. - Ningas, Celina
The study aims to describe and determine the relationship between exposure to pornographic materials (hardcore and sexually explicit pornographic materials) and men's sexism (hostile and benevolent sexist attitude) towards women. The study hypothesized that there is a significant relationship between exposure to pornographic materials and men's sexism towards women. With the use of descriptive research design with the aid of a survey questionnaaire to gather data with the application of Pearson Coefficient Correlation and Partial Correlation method, the relationship between the concepts understudy was obtained. Third year and fourth year male (260 college) students from four different schools in the city of Iloilo participated in the study. The study revealed that majority of the respondents is exposed to both hardcore and sexually explicit pornographic materials while very few reported having had no exposure at all. The study also shows that most of the respondents who participated in the study have a benevolent sexist attitude towards women rather than hostile one. The results show that there is no significant relationship between exposure to hardcore pornography and men's sexism towards women (both on hostile and benevolent sexist attitude towards women). On the other hand the study revealed that there is a positively significant relationship between exposure to sexually explicit pornographic materials and men's sexism towards women. Both hostile and benevolent sexist attitude towards women were significantly related to exposure to sexually explicit pornographic materials. In conclusion, the researchers could say that viewing hardcore pornographic materials has no harmful effects on the viewers since there were no relationship established in the study. Also the study concludes that viewing sexually explicit pornographic materials especially those depictions of women enjoying sexual promiscuousness and those that depicts women who threaten male superiority would tend to have an influence on the viewers' attitude towards women.